Cafeteria management and monitoring system - Tan, Kean Yew (2024)
This project is to create a cafeteria management and monitoring system. Basically, this system is a web application that allow user to get know of the cafeteria details and information by real time. It also allows cafeteria hawker to manage their cafeteria business such as update operating status and food menu. This system is different from existing system due to it not only show the cafeteria details and information but also show the sub stall in it. This is because there are a lot of cafeteria like kopitiam which there exist others stall inside the cafeteria in Malaysia. As a customer, we always hope to find those stalls information such as current operating status and what food is on sell currently. This system is a real time system that allow customer to check their interested cafeteria and food stall information from time to time. Furthermore, this system can help cafeteria hawker to improve their business and food as they can know customer feedback and suggestion through this system. The methodology that used to develop this system is prototyping, which is one of the RAD methods. The languages used in this system are HTML, CSS, JavaScript, jQuery, PHP and SQL. The database and web server used is phpMyAdmin and XAMPP server.